2015
DOI: 10.1002/smrj.56
|View full text |Cite
|
Sign up to set email alerts
|

Nitrergic Mechanisms for Management of Recurrent Priapism

Abstract: Introduction Priapism is a condition involving prolonged penile erection unrelated to sexual interest or desire. The ischemic type, including its recurrent variant, is often associated with both physical and psychological complications. As such, management is of critical importance. Ideal therapies for recurrent priapism should address its underlying pathophysiology. Aim To review the available literature on priapism management approaches particularly related to nitrergic mechanisms. Methods A literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Sickle cell patients with priapism have higher rates of hemolysis than sickle-cell men without priapism, as well as a higher red blood cell disaggregation threshold and lower red blood cell deformability, a pattern similarly found in sickle cell patients who experience leg ulcers and glomerulonephropathy ( 34 ). More recently, animal models and clinical studies have revealed a role for abnormal nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) signaling and regulation in the pathogenesis of stuttering priapism ( 35 - 40 ).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Sickle cell patients with priapism have higher rates of hemolysis than sickle-cell men without priapism, as well as a higher red blood cell disaggregation threshold and lower red blood cell deformability, a pattern similarly found in sickle cell patients who experience leg ulcers and glomerulonephropathy ( 34 ). More recently, animal models and clinical studies have revealed a role for abnormal nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) signaling and regulation in the pathogenesis of stuttering priapism ( 35 - 40 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…Improper PDE5 regulation and subsequent aberrant NO signaling appears to be an important cause of stuttering priapism ( Figure 1 ) ( 35 ). Production of PDE5 is cGMP-dependent, and a basal decrease in the activity of cGMP leads to transcriptional downregulation of PDE5, resulting in dysfunctional termination of the erectile response ( 40 ). The low basal levels of cGMP are thought to stem from decreased bioavailability of NO, which may be due to endothelial damage and decreased eNOS activity and scavenging of NO by reactive oxygen species or free hemoglobin released through hemolysis, particularly in sickle cell disease patients ( 45 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…Furthermore, randomized controlled trials targeting the NO pathway via PDE5 inhibition are underway, 38 and pharmacologic therapy involving either direct or indirect NO donation has recently been proposed to treat sickle cell disease patients suffering from priapism. 39,40…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies suggest daily administration of low-dose PDE-5 inhibitors after the acute period of priapism to upregulate PDE-5 gene expression, to stimulate eNOS expression and to reduce the state of dysfunctional NO pathway [ 21 ]. By doing so, such treatment could restore the balance between stimulating and inhibiting factors, thus reducing the episodes of priapism [ 22 ]. In a small case series, Burnett and colleagues [ 18 ] showed that daily PDE5 inhibitor therapy reduced ischemic priapism episodes in men with stuttering priapism, either idiopathic or due to sickle-cell disease, without modifying erectile function.…”
Section: Discussionmentioning
confidence: 99%